"Ti morš ja sam gledat, da se vključiš!" Participacija mladih Slovenk in Slovencev na dvojezičnem avstrijskem Koroškem - Vavti, Štefka (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2013)
The article presents a selection of the results of a qualitative research analyzing the situation of young Slovenes in the bilingual Carinthia, Austria. The target group of the survey are the young people, who live in Southern Carinthia, and the representatives of Slovene cultural associations. By reason of the biographical methodological approach, young interviewees have spoken about their lives and about their participation in the Slovene associations. What is their motivation to cooperate in cultural associations? Also the perspective and interpretation by leaders of these associations is from interest: In which fields they observe problems in participation of young Slovenes? The results to a large extent confirm the findings of international and national research that forecast a withdrawal of the young people form involvement in traditional associations towards private life. On the other hand, especially the young Slovenes cooperate with Slovene cultural associations and are active in theatre, chorus, puppet theatre etc., whereas interest in minority politics is decreasing.
Keywords: Austria; Avstrija; Carinthian Slovenes; koroški Slovenci; dvojezičnost; bilingualism; mladina; participacija; kulturna društva